Oral Tradition - A Literacy for Lifelong Learning: Native American Approaches to Justice and Wellness Education. - Marlene R. Atleo; Achaessa James (Adult Education Research Conference, 2000)
Native American oral tradition provides a literacy for lifelong learning that promotes perspective transformations. This approach is particularly suited to justice and wellness education because participants engage multiple ways of being and knowing: sensory, philosophical, serious, humorous, etc. Oral traditions can be understood in the context of transformative learning that has implications for adult education.